Meeting the infrastructure challenge in Latin America and the Caribbean. (Washington, D.C. World Bank, 1995)
"Summarizes argument that increased infrastructure expenditures are critically needed to accelerate regional growth. Discusses power, telecommunication, transportation, water and sewerage facilities, etc. Emphasizes means of financing these projects"- -Handbook of Latin American Studies, v. 57.
Keywords: Karibik; Lateinamerika